Analisis Pengaruh Variabel-Variabel Makroekonomi terhadap Tingkat Pengembalian di Pasar Modal Periode 2000 -2011 dengan Membandingkan Hasil Estimasi OLS, GLS dan MLE - Damayanti, Sari Minjari (Bina Nusantara University, 2014)
The factors in macroeconomic gives enormous influence on the fluctuation rate of return on stocks that is reflected in the stock price movement in the stock market. Movements in excess of the normal state, such as those caused by the global economic crisis, from the macro variables will create specific shocks on the capital markets, which will affect the value of the return on stocks in the capital market. To determine the effect of the factors or macroeconomic variables on the return of the index shares on BEI, empirical tests are accurately performed on these variables. This study has two main objectives: first to test how much the influence of macroeconomic variables on the return of the shares in the Indonesian Stock Exchange (BEI). Second, empirical research testing of variables using three different estimation methods, namely, Ordinary Least Squares (OLS), Generalized Least Square (GLS) and Maximum Likelihood Estimation (MLE) to find out how much the estimation accuracy of the three methods. The empirical result shows that there is a significant relationship between composite stock returns BEI and three macroeconomic variables, the consumer price index (inflation rate), exchange rate and interest rate of SBI. These results indicate that the three macro variables that affect the rate of return on the stock market.